Metabolic correction of experimental diabetic retinopathy - I.V. Savitskyi; V.V. Semenko; V.M. Serdiuk (Ukrainian Society of Ophthalmologists, 2017)
Introduction. Diabetic retinopathy (DR) is diagnosed in 50% of the total number of patients suffering from type 1 diabetes mellitus with diabetes duration of over 10 years and in 75-90% of patients with diabetes duration over 15 years. Purpose. To ground the possibility of using arginine for correction of vascular changes in the eye at early stage of DR. Materials and Methods. The study involved outbred white Wistar rats divided into three groups: Group 1, unexposed animals served as controls (Control group); Group 2, animals with a diabetes mellitus model (DM group); Group 3, diabetic animals which received 7% arginine solution (DM+arginine group). Results. Glucose test revealed no significant difference between Group 1 and Group 3 (р=0.14) while the difference was highly significant between Groups 2 and 3 (р=0.0019). Histological study of the eyeball tissues showed that fibers were not combined into the homogeneous mass, separate fibers could be defined. In the photoreceptor layer, structural elements were pale stained but had high density of distribution. The outer granular layer of the retina was characterized by nuclei with rather dense distribution to each other. The nuclei were relatively large, round, and brightly stained. The inner granular layer corresponded to the description of the outer granular layer. In the ganglion cell layer, neuron nuclei were round, well-stained and distributed rather evenly. Conclusions. Arginine enabled to preserve the structure and functions of vessels and to reduce the disease severity.